Volatility and water efficiency of food crops in arid regions - Sari, Winda (Professorline, 2024)
Transpiration is the process by which water evaporates from the surface of plants, especially leaves. Transpiration is essential in transporting water and nutrients from the roots to the top of the plant and cooling the plant. However, evaporation also causes water loss, limiting plant growth and production in dry areas. Therefore, water efficiency, or the relationship between crops and water consumption, becomes one of the most critical indicators to increase the productivity of crops in dry areas. This article discusses the factors that affect evapotranspiration and water efficiency of food crops, as well as strategies to reduce evapotranspiration and improve water efficiency in arid regions. Some strategies discussed include selecting drought-tolerant varieties, spacing and planting methods, weed control and mulching, and inadequate irrigation. This document should provide information and inspiration to scientists, farmers and decision-makers facing the growing challenge of drought caused by climate change.